Bovine Tuberculosis and the Establishment of an Eradication Program in the United States: Role of Veterinarians - Mitchell V. Palmer; W. Ray Waters (Veterinary Medicine International)
The significance of the identification of Mycobacterium bovis as a zoonotic pathogen in 1882 was not initially recognized. After years of research by veterinarians, and other scientists, the importance of M. bovis as a pathogen and the public health ramifications, were appreciated. Veterinarians played pivotal roles in the creation of improved meat and milk inspection, diagnosis of M. bovis infected cattle, and in time, a bovine tuberculosis eradication program that would impact every cattle producer in the country. After overcoming many challenges, the 93-year-long program has decreased disease prevalence from 5% to <0.001%. Today, years of hard work by practitioners, researchers and regulatory officials alike, have yielded a program with a net benefit of almost $160 million per year.